2019
DOI: 10.32582/aa.60.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric measurements of newborn blue shark Prionace glauca (Linnaeus, 1758) and characteristics of its potential parturition areas in coastal waters of Montenegro (Southeastern Adriatic)

Abstract: The blue shark belongs to the group of the most widespread pelagic sharks in the world. It inha-bits the pelagic zone of almost all warm and temperate seas and oceans. As it is one of the most abundant shark species, it is frequently caught in different types of fishing gear operated in the pela-gic zone. This study provides the first data on the reproduction of this species in Montenegrin waters (in the Southeastern Adriatic Sea). Six newborn blue sharks were found during our field excursions. For three of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…From each record, the following information was collected: (i) date and location; (ii) type of record, which included four standard categories – sightings of blue sharks swimming in inshore waters, swimming in confined areas (tourist hotspots, commercial ports, and artificial and/or natural lagoons), stranding, and by‐catch; (iii) number of individuals for each record; (iv) sex of each shark, determined, when possible, by visually examining the pelvic fins for the presence of claspers in males or their absence in females; (v) life stage, classed according to Leone et al (2017) as juvenile, with an estimated total length (ETL) of ≤120 cm, subadult, with an ETL of 120–180 cm, and adult, with an ETL of >180 cm (within the juvenile life stage, a subcategory was used to identify smaller individuals with an ETL of <80 cm, based on TL < 81.7 cm (Megalofonou, Damalas & De Metrio, 2005a), considered to be young‐of‐the‐year (YOY) (Ćetković et al, 2019; Nosal et al, 2019), and identified with an asterisk in Table S1); and (vi) biological and/or ecological observations, including pregnancy, wounds, presence of fishing gear, professional rescue operations, etc.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From each record, the following information was collected: (i) date and location; (ii) type of record, which included four standard categories – sightings of blue sharks swimming in inshore waters, swimming in confined areas (tourist hotspots, commercial ports, and artificial and/or natural lagoons), stranding, and by‐catch; (iii) number of individuals for each record; (iv) sex of each shark, determined, when possible, by visually examining the pelvic fins for the presence of claspers in males or their absence in females; (v) life stage, classed according to Leone et al (2017) as juvenile, with an estimated total length (ETL) of ≤120 cm, subadult, with an ETL of 120–180 cm, and adult, with an ETL of >180 cm (within the juvenile life stage, a subcategory was used to identify smaller individuals with an ETL of <80 cm, based on TL < 81.7 cm (Megalofonou, Damalas & De Metrio, 2005a), considered to be young‐of‐the‐year (YOY) (Ćetković et al, 2019; Nosal et al, 2019), and identified with an asterisk in Table S1); and (vi) biological and/or ecological observations, including pregnancy, wounds, presence of fishing gear, professional rescue operations, etc.…”
Section: Methodsmentioning
confidence: 99%
“…between the intertidal zone and an arbitrary cutoff set at approximately 100 m offshore. (Toivonen et al, 2019) dedicated to marine biodiversity, conservation, recreational diving and recreational fishery or specifically focused on elasmobranch sightings (Bargnesi, Lucrezi & Ferretti, 2020) Leone et al (2017) as juvenile, with an estimated total length (ETL) of ≤120 cm, subadult, with an ETL of 120-180 cm, and adult, with an ETL of >180 cm (within the juvenile life stage, a subcategory was used to identify smaller individuals with an ETL of <80 cm, based on TL < 81.7 cm (Megalofonou, Damalas & De Metrio, 2005a), considered to be young-of-the-year (YOY) ( Cetkovi c et al, 2019;Nosal et al, 2019), and identified with an asterisk in Table S1); and (vi) biological and/or ecological observations, including pregnancy, wounds, presence of fishing gear, professional rescue operations, etc.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation